2007
DOI: 10.1258/135763307780908049
|View full text |Cite
|
Sign up to set email alerts
|

Teleconsultation for emergency orthopaedic patients using the multimedia messaging service via mobile phones

Abstract: We investigated the accuracy and usefulness of teleconsultation using the mobile phone multimedia messaging service (MMS) in emergency orthopaedic patients. Pictures of radiographs were taken using a built-in 1.3 megapixel mobile phone camera from a digital display screen in the emergency room and then transmitted to the camera phones of four assessors. The cases comprised 59 emergency orthopaedic patients diagnosed with non- or minimally displaced fractures and 34 age-matched normal patients visiting the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 11 publications
1
53
0
Order By: Relevance
“…In five of the nine other studies that assessed systems at the pilot or post-implementation stages, the assessors considered cases through the telemedicine modality only [22], [23], [32], [35], [39]; in two, both telemedicine and on-site interpretations were done one after the other [40], [41]. In two articles a telephone description was compared to the telemedicine modality [31], [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In five of the nine other studies that assessed systems at the pilot or post-implementation stages, the assessors considered cases through the telemedicine modality only [22], [23], [32], [35], [39]; in two, both telemedicine and on-site interpretations were done one after the other [40], [41]. In two articles a telephone description was compared to the telemedicine modality [31], [42].…”
Section: Resultsmentioning
confidence: 99%
“…In two articles a telephone description was compared to the telemedicine modality [31], [42]. Three evaluations used a gold standard [22], [23], [39], and statistical analysis included kappa, correlation coefficient and descriptive statistics, and accuracy analysis (sensitivity and specificity). Results showed generally good diagnostic accuracy, except in one study [39].…”
Section: Resultsmentioning
confidence: 99%
“…(Currell et al, 2000) For example, in one study, transmitting x-ray radiographs to a remote orthopedic surgeon using the mobile phone MMS (multimedia messaging service) resulted in under or over diagnosing that would have led to mismanagement in 48% of the cases. (Chandhanayingyong et al, 2007) Definitely, there are some limitations to the accuracy of the physical exam using teleconsultation such as the lack of palpation and smell. (Boodley, 2006) 2.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, telecommunication is obviously less robust in terms of physical examination, and there is a danger that physical signs will be missed. 16 Furthermore, patients and physicians share some concerns regarding communication technology. 17 Security and confidentiality are a particular concern with e-mail and Web.…”
Section: Communication Technology Usage In Cardiac Patientsmentioning
confidence: 99%
“…However, studies have shown that if support is given, new technologies can be successfully used even in very elderly populations. 16 Another concept is that of ''teleassistance'' where individuals in the community facilitate communication between physicians via telemedicine; these individuals could be community nurses, general practitioners, or others, although using non-healthcare professionals may be ethically challenging, and confidentiality of patients should always be protected.…”
Section: Implications For Older Patientsmentioning
confidence: 99%